Pengaruh Pengalaman, Pelatihan, dan Beban Kerja terhadap Kemampuan Auditor dalam Pendeteksian Kecurangan: Studi KAP KKSP - Fitriningsih, Amelia; Ardiami, Kinanthi Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to examine the effect of experience, training, and workload on the auditor's ability to detect fraud. In this study using the type of research in the form of quantitative data with a causal relationship approach. The population in this study were auditors who worked at KAP KKSP with a total of 35 respondents. The sampling technique used in this research is nonprobability sampling using saturated sampling technique. Data collection techniques in this study used questionnaires and interviews with auditors as primary data. For data that is processed using multiple linear regression analysis to test the hypothesis. Based on the results of data processing, it can be concluded that the experience variable has a positive effect on the auditor's ability to detect fraud, the training variable has a positive effect on the auditor's ability to detect fraud, and the workload variable has no effect on the auditor's ability to detect fraud. Keywords: Experience, Training, Workload, Auditor's Ability in Fraud Detection.